EVALUASI SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA (SIMAK BMN) PADA KANTOR IMIGRASI KELAS II TAHUNA - Majampoh, Greise; Saerang, David Paul Elia; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The State Property Management and Accounting Information System is a technology based apllication system implemented in the Class II Tahuna Immigration Office, with the aim of dealing with administration mainly covering state-owned assets. This study aimsto evaluate the performance of SIMAK BMN insupporting asset inventory at Tahuna Immigration Office. The research method is case study using descriptive research method. The data used are secondary data and primary data. With the technique of collecting interview data and documentation. The results of this study revealed that the work of SIMAK BMN can be viewed from the quality of information, Timeliness, ease of use SIMAK BMN and supporting and inhibiting factors. Of the four (4) points it is found that in the quality of information generated SIMAK BMN is very influential on the financial statements Immigration Office Tahuna, but there are still some factors that inhibit the work of SIMAK BMN from SIMAK BMN and SIMAK BMN which is often wrong in the error.Â  Keywords: Management Information System and Accounting of State Property (SIMAK BMN)